Nickel–copper supported on a carbon black hydrogen oxidation catalyst integrated into an anion-exchange membrane fuel cell. Issue 10 (9th August 2018) - Roy, Aaron; Talarposhti, Morteza R.; Normile, Stanley J.; Zenyuk, Iryna V.; De Andrade, Vincent; Artyushkova, Kateryna; Serov, Alexey; Atanassov, Plamen
Abstract : This work introduces the first practical platinum group metal-free (PGM-free) electrocatalyst for the hydrogen oxidation reaction (HOR) in alkaline membrane fuel cells (AMFC), based on nickel-rich Ni95 Cu5 -alloy nanoparticles. Abstract : This work introduces the first practical platinum group metal-free (PGM-free) electrocatalyst for the hydrogen oxidation reaction (HOR) in alkaline membrane fuel cells (AMFCs), based on nickel-rich Ni95 Cu5 -alloy nanoparticles supported on Ketjenblack (KB) family carbon blacks. The catalyst synthesis is scalable and results in an expected true alloy of NiCu, which is thoroughly characterized by XRD, microscopy and XPS. The reactivity of the catalyst towards the HOR is studied by cyclic voltammetry and explained in view of its composition and structure. This catalyst showed the highest specific activity compared to previously reported NiCu electrocatalysts and was successfully integrated into an AMFC membrane electrode assembly (MEA) using a commercially available state-of-the-art membrane and an ionomer. Single MEA fuel cell tests have demonstrated a power density of 350 mW cm −2 at 80 °C, which sets a technical record for a PGM-free anode in realistic operating conditions. The MEA with the NiCu/KB anode catalyst layer was evaluated by in situ nano- and in operando micro-X-ray computed tomography (CT) and the results suggest that the nickel state in NiCu is hydrophobic in nature, where the NiCu surface may be isostructural with β-Ni(OH)2 . The hydrophobic nature of the electrocatalyst allows for improved water distribution in the MEA and overall fuel cell as observed by in operando micro-X-ray CT.